Band gap tuning of Ni1−xMgxO films by radio-frequency sputter deposition for deep-ultraviolet photodetectors. (16th September 2015) - Nishitani, Hiroki; Ohta, Kohei; Kitano, Sosuke; Hamano, Ryosuke; Inada, Mitsuru; Shimizu, Tomohiro; Shingubara, Shoso; Kozuka, Hiromitsu; Saitoh, Tadashi
Abstract: A deep-ultraviolet photodetector based on a Ni0.52 Mg0.48 O film was fabricated using a simple radio-frequency sputtering technique and a Ni–Mg composite target. The Ni1− x Mg x O band gap can be tuned by adjusting the Mg content, which in turn can be controlled by varying the number of Mg chips on the Ni target. The lattice constant of Ni1− x Mg x O linearly depends on the Mg content, whereas the plot of the band gap versus Mg content exhibits bowing. The fabricated photodetector based on the Ni0.52 Mg0.48 O film operates as a deep-ultraviolet photodetector and shows peak responsivity at a wavelength of 276 nm.